Testing Effects of Changes in Earnings to Dividend Actions of Listed Firms on Vietnamese Stock Exchanges Using the Multinomial Logistic Regression Model - Dinh, Nguyen Van; Yen, Nguyen Thi Hai (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 2, 2018)
This paper aims to fill the gap in dividend policy researches of listed companies in Vietnam stock exchanges. Effects of changes in earning to changes in dividend actions of selected listing firms are tested in order to figure out their relationships. The multinomial logistic regression model is employed with the data from a balanced panel of 2,790 firm-year observations representing 310 listed firms in both Ho Chi Minh City Stock Exchange and Hanoi Stock Exchange during the 9-year period from 2008 to 2016.    The study has estimated odds and odds ratios of four dividend change cases in responses to each of three cases of earning changes. The results shows that: When earnings increase, the probability that firms increase dividend is 55%, higher than probabilities that firms keep dividend unchanged, decrease dividend or no dividend of, 26%, 13% and  6% respectively, all at significance of 1%; When earnings decrease, the probability that firms reduce dividend is 44%, higher than probabilities that firms increase, keep dividend unchanged, or pay no dividend of, 20%, 27% and  9% respectively, all at significance of 1%; When firm had negative earning, probability that firm pay no dividend is 86% (at significance of 1%), that is much higher than probability that firms reduce dividend (8%, at all at significance of 5%); The results are supportive to the hypothesis that dividend actions are strongly affected by firms’ earnings and past dividend actions. The research results are meaningful to dividend income investors in formulating their investment strategies and for management of firms in designing firms’ dividend policies.